1994
DOI: 10.1021/bi00191a006
|View full text |Cite
|
Sign up to set email alerts
|

Solution Structure of Residues 1-28 of the Amyloid .beta.-Peptide

Abstract: The three-dimensional solution structure of residues 1-28 of the amyloid beta-peptide was determined using nuclear magnetic resonance spectroscopy, distance geometry, and molecular dynamic techniques. The nuclear magnetic resonance data used to derive the structure consisted of nuclear Overhauser enhancements, vicinal coupling constants, and temperature coefficients of the amide-NH chemical shifts. The beta-peptide is the major proteinaceous component of amyloid deposits in Alzheimer's disease. In membrane-lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
183
0
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(206 citation statements)
references
References 87 publications
22
183
0
1
Order By: Relevance
“…There is also a weak NOE between the upfield 5′H and the 4′CH 2 . In the NOESY spectrum of the peptide alone ( Figure 6B), the NOEs are analogous to spectra that we published earlier (Talafous et al, 1994), and the assignments of the Lys16 side chain resonances are shown along the diagonal. For the NOESY spectrum of the mixture ( Figure 6C), other than the His residues, there are no apparent changes in chemical shifts for the peptide resonances, and new NOEs were not detected between the peptide and nicotine.…”
Section: Shown Insupporting
confidence: 61%
See 2 more Smart Citations
“…There is also a weak NOE between the upfield 5′H and the 4′CH 2 . In the NOESY spectrum of the peptide alone ( Figure 6B), the NOEs are analogous to spectra that we published earlier (Talafous et al, 1994), and the assignments of the Lys16 side chain resonances are shown along the diagonal. For the NOESY spectrum of the mixture ( Figure 6C), other than the His residues, there are no apparent changes in chemical shifts for the peptide resonances, and new NOEs were not detected between the peptide and nicotine.…”
Section: Shown Insupporting
confidence: 61%
“…In the past our laboratory has used these methods for studies of the -peptide [see Talafous et al (1994) and references cited therein]. The results shown here establish that these methods can be successfully applied to investigate inhibitors of -amyloidosis and their binding properties.…”
Section: Biological Functions Of Nicotine and Its Relevance To Alzheimentioning
confidence: 53%
See 1 more Smart Citation
“…NMR is an excellent technique for determining the high resolution structure of peptides, but early NMR studies of the A␤ were hindered by the strong tendency of this peptide to aggregate, particularly near pH 5, where it forms a ␤-sheet-rich oligomer that precipitates. This obstacle was first surmounted by the pioneering studies of Zagorski and co-workers, who used cosolvents (18) and detergents (19) to solubilize monomeric A␤. NMR studies of monomeric A␤ in organic solvents (20), in cosolvents (18,21), or associated with detergent micelles (19,(22)(23)(24) revealed extensive helix formation.…”
mentioning
confidence: 99%
“…The amyloid ß (1-28) peptide obtained from the protein data bank (PDB) has several confor mational structures determined via NMR in solu tion (Barrow and Zagorski, 1991;Zagorski and Barrow, 1992;Talafous et al, 1994). These struc-tures have been averaged and the starting coordi nates for this peptide were obtained and used to perform the calculations of water accessibility to the aspartyl residues at positions 7 and 23.…”
Section: Methodsmentioning
confidence: 99%